PERAN KOMUNIKASI DALAM KEPEMIMPINAN EFEKTIF PADA ORGANISASI MAHASISWA - Saleh, Munandi; Heryadi, Ahmad Irwan; Kambali, Laraswati; Aspirani, Anisa; Abdullah, Abdullah (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
Research on the role of communication in effective leadership has been done by many researchers before, but it is still rare to conduct research with loci in student organizations. This study aims to discover and explain communication's role in effective leadership in UMMI student organizations. Quantitative descriptive is used as the method of this research, while as a sample, namely representatives from each student organization, in this case the secretary and members totaling 88 respondents. Questionnaires were distributed to respondents as a data collection method for this study. The study's results explained that communication had a significant positive influence on effective leadership, with an influence of 61.6%.